Do markets care about Central Bank governor changes? Evidence from emerging markets - Christoph Moser; Axel Dreher (ETH Zurich, KOF Swiss Economic Institute, 2007)
Central bank governor changes in emerging markets may convey important signals about future monetary policy. Based on a new daily data set, this paper examines the reactions of foreign exchange markets, domestic stock market indices and sovereign bond spreads to central bank governor changes. The data cover 20 emerging markets over the period 1992-2006. We find that the replacement of a central bank governor negatively affects financial markets on the announcement day. This negative effect is mainly driven by irregular changes, i.e., changes occurring before the scheduled end of tenure, sending negative signals about perceived central bank independence. Personal characteristics of the central banker, to the contrary, are less important for market reactions. We find no evidence that changes in the central banker's conservatism affect the reactions of the markets. Finally, market reactions are similar in countries with high and low degrees of central bank independence.
Keywords: E58; E42; F30; G14; 330; central bank governor turnover; monetary policy; emerging markets; risk premium; Geldpolitik; Führungskräfte; Zentralbank; Finanzmarkt; Ankündigungseffekt; Schwellenländer